2019
DOI: 10.1016/s0140-6736(19)31288-7
|View full text |Cite|
|
Sign up to set email alerts
|

HIV incidence among women using intramuscular depot medroxyprogesterone acetate, a copper intrauterine device, or a levonorgestrel implant for contraception: a randomised, multicentre, open-label trial

Abstract: Summary Background Observational and laboratory studies suggest that some hormonal contraceptive methods, particularly intramuscular depot medroxyprogesterone acetate (DMPA-IM), might increase women's susceptibility to HIV acquisition. We aimed to compare DMPA-IM, a copper intrauterine device (IUD), and a levonorgestrel (LNG) implant among African women seeking effective contraception and living in areas of high HIV incidence. Methods We did a randomised, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
206
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(224 citation statements)
references
References 18 publications
7
206
1
Order By: Relevance
“…Notably, these findings have not been consistently demonstrated by all studies, and all the studies were observational thus prone to potential confounding. Further, the findings have been challenged by the results from the Evidence for Contraceptive Options and HIV outcomes (ECHO) study [4], a large randomized trial that found no significant increase in HIV risk among users of DMPA compared to copper intrauterine device and levonorgestrel implant users. While these data are reassuring, gaps remain in our understanding of the relative HIV risk with contraceptive use compared to non-use and the impact of other progestin-containing contraceptive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these findings have not been consistently demonstrated by all studies, and all the studies were observational thus prone to potential confounding. Further, the findings have been challenged by the results from the Evidence for Contraceptive Options and HIV outcomes (ECHO) study [4], a large randomized trial that found no significant increase in HIV risk among users of DMPA compared to copper intrauterine device and levonorgestrel implant users. While these data are reassuring, gaps remain in our understanding of the relative HIV risk with contraceptive use compared to non-use and the impact of other progestin-containing contraceptive methods.…”
Section: Introductionmentioning
confidence: 99%
“…An area that has shown success in long‐acting drug delivery modalities are injectable contraceptives which are used by 25% of South African women aged 15 to 49 years . While some observational studies suggested progesterone‐based injectables, particularly depot medroxyprogesterone acetate (DMPA), might increase the risk of HIV infection , a recent randomized controlled study did not find an increased risk for HIV for women using DMPA as compared to women using other contraceptive methods . However, women using injectable contraceptives might still be an interesting target population for injectable forms of long‐acting PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…The study was designed to address whether there is an increased risk of HIV acquisition when comparing women using DMPA with Cu-IUD, DMPA with levonorgestrel implant, and Cu-IUD with levonorgesterel implant. The results from the trial were published in mid-2019, and show that there is not an increased risk of HIV incidence among users of DMPA as compared to users of Cu-IUD or the implant [2]. The findings support the continued use of these methods in areas of high incidence of HIV.…”
Section: Introductionmentioning
confidence: 84%
“…The findings support the continued use of these methods in areas of high incidence of HIV. However, the overall HIV incidence in the study population was 3.8 per 100 woman-years, which is "alarmingly high", and signals a need for strengthened family planning (FP)/HIV programming [2].…”
Section: Introductionmentioning
confidence: 91%